Inkerikot, setot ja vatjalaiset Kansankulttuuri, kieli ja uskomusperinteet - Kallio, Kati; Grünthal, Riho; Saressalo, Lassi (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
The book focuses on intangible and tangible heritage, language and vernacular religion of the Ingrians, Setos and Votes, three Finnic ethnic minorities sharing a long-standing identification with the Russian Orthodox faith. Written by 16 authors, the chapters are mainly based on nineteenth- and twentieth-century materials. The research history and collecting of folklore are also discussed.The historical area of the Ingrians and Votes is located in Ingria, adjacent to St. Petersburg, while the Setos have inhabited both sides of the border of southern Estonia and Russia. All three groups live on the borderline of the Eastern and Western Churches and cultural realms.Currently, the Ingrian and Votic languages are extremely endangered, while the Seto language has approximately 12,000 speakers. There is a high local interest in the maintenance and revitalisation of all three languages and cultural traditions.